Functional specialization of Aurora kinase homologs during oogenic meiosis in the tunicate Oikopleura dioica - Feng, Haiyang; Thompson, Eric M. (Frontiers in Cell and Developmental Biology, 2023)
A single Aurora kinase found in non-vertebrate deuterostomes is thought to represent the ancestor of vertebrate Aurora A/B/C. However, the tunicate Oikopleura, a member of the sister group to vertebrates, possess two Aurora kinases (Aur1 and Aur2) that are expressed in proliferative cells and reproductive organs. Previously, we have shown that Aurora kinases relocate from organizing centers (OCs) to meiotic nuclei and were enriched on centromeric regions as meiosis proceeds to metaphase I. Here, we assessed their respective functions in oogenic meiosis using dsRNA interference. We found that Aurora1 was involved in meiotic spindle organization and chromosome congression, probably through regulation of microtubule dynamics, whereas Aurora2 was crucial for chromosome condensation and meiotic spindle assembly. In vitro kinase assays showed that Aur1 and Aur2 had comparable levels of kinase activities. Using yeast two-hybrid library screening, we identified a few novel interaction proteins for Aur1, including c-Jun-amino-terminal kinase-interacting protein 4 (JIP4), cohesin loader SCC2, and mitochondrial carrier homolog 2 (MTCH2), suggesting that Aur1 may have an altered interaction network and participate in the regulation of microtubule motors and cohesin complexes in O. dioica.